Pengaruh Intelligence Quotient, Emotional Quotients, Spiritual Intelligence dan Kecerdasan Adversitas Terhadap Tingkat Pemahaman Mata Kuliah Akuntansi - Nurul Indah Q. Muksin; Maslichah Maslichah; Umi Nandiroh (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study was to find out how the influence of intelligence quotient, emotional quotients, spiritual intelligence and adversity intelligence on the level of understanding of accounting courses in accounting students in Ternate. The variables used in this study consisted of independent variables: intelligence quotient, emotional quotients, spiritual intelligence and adversity intelligence. Dependent variable: understanding of accounting. This research was conducted from February to completion at three universities in the city of Ternate. Namely, Muhammadiyah University of North Maluku, Khairun University of Ternate, and Ternate State Institute of Islamic Religion. Descriptive analysis, classical acceptance test, and multiple regression analysis were used in this research data analysis technique. Students majoring in accounting class of 2020 at North Maluku Muhammadiyah University, Khairun University Ternate, and Ternate State Institute of Islamic Religion. sample and through criteria: 1) S1 students majoring in accounting class of 2020 who are still active. 2) Have completed the courses Introduction to Accounting, Financial Accounting 1, Financial Accounting 2, Advanced Financial Accounting 1, Advanced Financial Accounting 2, Auditing, Accounting Theory. as sample. The results of this study indicate that intelligence quotient, emotional quotients, spiritual intelligence and adversity intelligence simultaneously have a significant positive effect on accounting comprehension.Keywords: Intelligence quotient, emotional quotients, spiritual intelligence, adversity intelligence, understanding of accounting.